BARIERY W NAUCE JĘZYKÓW OBCYCH – PERSPEKTYWA UCZĄCYCH SIĘ - Smuk, Maciej (Neofilolog, 2018)
This article’s main aim is to present the results of research concerning the barriers in foreign language learning. It analyses various obstacles indicated by 342 students from both philological and non-philological departments. Those factors have been subdivided into three groups, each dealing with a different type of barriers: external objective barriers, barriers associated with behavior and competence of the teacher as well as concerning language courses, and, finally, cognitive, affective, and personality related barriers.